PERBANDINGAN SISTEM HUKUM PIDANA DALAM PERLINDUNGAN DATA PRIBADI DI INDONESIA, JERMAN, DAN SINGAPURA: TANTANGAN DAN REFORMASI HUKUM DI ERA DIGITAL - Melinda Ratnawati; Moch. Eko Setiyo Budi Utomo (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2026)
The rapid advancement of digital technology has significantly transformed the ways individuals, businesses, and governments collect, process, and utilize personal data. Alongside these developments, concerns regarding data breaches, unauthorized access, identity theft, and violations of privacy rights have become increasingly prominent. Personal data protection has therefore emerged as a critical contemporary legal issue requiring effective legal frameworks and enforcement mechanisms. This study aims to compare the criminal law approaches to personal data protection in Indonesia, Germany, and Singapore. The research employs a normative legal research method using statutory, conceptual, and comparative law approaches. The findings reveal that Indonesia has established a legal foundation through Law Number 27 of 2022 concerning Personal Data Protection; however, challenges remain regarding institutional capacity and law enforcement effectiveness. Germany, through the General Data Protection Regulation (GDPR), has developed a comprehensive legal framework supported by strong independent supervisory authorities and strict sanctions. Singapore adopts a pragmatic and business-oriented approach through the Personal Data Protection Act (PDPA), emphasizing regulatory compliance, accountability, and support for the digital economy. While all three countries recognize personal data protection as a legal right and provide sanctions for violations, significant differences exist in terms of supervisory structures, enforcement mechanisms, and regulatory effectiveness. The study concludes that Indonesia can strengthen its personal data protection regime by establishing an independent supervisory authority, enhancing enforcement capabilities, improving inter-agency coordination, and adopting best practices from Germany and Singapore. Such reforms are essential to ensure stronger legal protection, public trust, and sustainable digital governance in the era of rapid technological development.